Transcending patterns: silk road cultural and artistic interactions through central Asian textile images - Gasparini, Mariachiara (Perspectives on the global past, 2020)
In 'Transcending Patterns: Silk Road Cultural and Artistic Interactions through Central Asian Textiles', Mariachiara Gasparini investigates the origin and effects of a textile-mediated visual culture that developed at the heart of the Silk Road between the seventh and fourteenth centuries. Through the analysis of the Turfan Textile Collection in the Museum of Asian Art in Berlin and more than a thousand textiles held in collections worldwide, Gasparini discloses and reconstructs the rich cultural entanglements along the Silk Road, between the coming of Islam and the rise of the Mongol Empire, from the Tarim to Mediterranean Basin. Exploring in detail the iconographic transfer between different agents and different media from Central Asian caves to South Italian churches, the author depicts and describes the movement and exchange of portable objects such as sculpture, wall painting, and silk fragments across the Asian continent and across the ages